Body, Meanings, and Physical Exercise in Older Adults: The Qualitative Perspective of Frequent Gym-Goers - Sossa Rojas, Alexis (Qualitative Sociology Review, 2022)
It is known that rates of participation in sports and physical activities among older adults decrease as they get older. This article focuses on the experience of the aging body at the gym, and it is one of the few that focuses on a little-studied group of frequent gym-goers. Based on an ethnographic work of more than two years in Amsterdam, I explain the goals of three older adults who frequently work out, what their relationships with the gym and their bodies are, and why they are interested in training in gyms. This article seeks to contribute to discourses on health, sport, and aging and, at the same time, to explain some of the advantages of qualitative studies in understanding the experience of aging and training in gyms.